Flood Analysis of the Kedung Ingas River and Pabean River the Cilegon City - Waita, Stanley Reynaldi Frits Sirway; Priyambodho, Bambang Adhi; Purnaditya, Ngakan Putu; Fathonah, Woelandari; Subekti, Subekti; Nabila, Firyaal (JURUSAN TEKNIK SIPIL, 2025)
The Kedung Ingas River and Pabean River the Cilegon City often flood every year. It has an impact on losses and disruptions to public facilities and settlements such as highways, Cilegon Regional Hospital, Metro housing and residential areas located close to the river. The purpose of this study is to determine the amount of design discharge at 10, 25 and 50 years return period. The methods used to calculate the design flood discharge are Rational, Der Weduwen, and HSS Nakayasu. Based on the results of the study, the design flood discharge of the Kedung Ingas River and the Pabean River with Q10 = 121.25 m3/s, Q25 = 131.01 m3/s, and Q50 = 138.79 m3/s. The design flood discharge value used is the calculation value using the selected method, namely Nakayasu Synthetic Unit Hydrograph.